Pelatihan Penggunaan Ponsel Pintar untuk Produksi Video Jurnalisme Warga bagi Pelajar dan Mahasiswa - Djamal, Muchamad Fauzi (Jurnal Pustaka Dianmas, 2025)
The number of smartphone users in Indonesia continues to increase and is dominated by young people, especially students and college students. However, the use of smartphones still tends to be limited to entertainment activities such as social media and online games, which are not optimal for productive activities such as making citizen journalism videos. This community service activity aims to educate and equip a group of high school students and students with the ability to use smartphones in creating citizen journalism works. The activity was carried out through a training method that combined theory delivery with hands-on practice and interactive discussions. Participants are trained to master basic journalistic skills, including mobile journalism techniques, interviews, writing, and video editing via smartphones. The results of the training showed a significant improvement in the participants' skills, which were measured through four main indicators, namely mastery of shooting techniques, video editing skills, video production skills, and understanding of citizen journalism. These findings imply that through measurable training, smartphones can be transformed from entertainment tools into productive equipment and encourage the younger generation to create citizen journalism videos that have a wide impact on society.